Healthy Living for Elders: Use Your Medicines Safely! - Paulina Wittkowsky (EDIS)
Medicines can help us feel better. But they can also harm us if they are not used correctly. To use your medicines safely, keep in mind the tips provided in this leaflet. This document, FCS8594-Eng, is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.